Methodology to define biological reference values in the environmental and occupational fields: the contribution of the Italian Society for Reference Values (SIVR) - Aprea, Maria Cristina; Scapellato, Maria Luisa; Valsania, Maria Carmen; Perico, Andrea; Perbellini, Luigi; Ricossa, Maria Cristina; Pradella, Marco; Negri, Sara; Iavicoli, Ivo; Lovreglio, Piero; Salamon, Fabiola; Bettinelli, Maurizio; et al. (La Medicina del Lavoro, 2017)
Background: Biological reference values (RVs) explore the relationships between humans and their environment and habits. RVs are fundamental in the environmental field for assessing illnesses possibly associated with environmental pollution, and also in the occupational field, especially in the absence of established biological or environmental limits. Objectives: The Italian Society for Reference Values (SIVR) determined to test criteria and procedures for the definition of RVs to be used in the environmental and occupational fields. Methods: The paper describes the SIVR methodology for defining RVs of xenobiotics and their metabolites. Aspects regarding the choice of population sample, the quality of analytical data, statistical analysis and control of variability factors are considered. The simultaneous interlaboratory circuits involved can be expected to increasingly improve the quality of the analytical data. Results: Examples of RVs produced by SIVR are presented. In particular, levels of chromium, mercury, ethylenethiourea, 3,5,6-trichloro-2-pyridinol, 2,5-hexanedione, 1-hydroxypyrene and t,t-muconic acid measured in urine and expressed in micrograms/g creatinine (μg/g creat) or micrograms/L (μg/L) are reported. Conclusions: With the proposed procedure, SIVR intends to make its activities known to the scientific community in order to increase the number of laboratories involved in the definition of RVs for the Italian population. More research is needed to obtain further RVs in different biological matrices, such as hair, nails and exhaled breath. It is also necessary to update and improve the present reference values and broaden the portfolio of chemicals for which RVs are available. In the near future, SIVR intends to expand its scientific activity by using a multivariate approach for xenobiotics that may have a common origin, and to define RVs separately for children who may be exposed more than adults and be more vulnerable.